Oblicza sukcesu edukacyjnego widziane przez pryzmat pokonywanych trudności w nauce gry na skrzypcach - Zwiercan, Halina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Presented issue describes a different dimension to educational success. This success is characterized by showing the achievements of capable students – winners of music competitions, and by showing the results of students with learning difficulties – children with smaller musical abilities: less precise ear for music, worse sense of rhythm and weaker music’s memory. Presented issue shows also the success of left-handed children to overcome the problems of using right hand in running the bow.
Keywords: muzyka; osiągnięcia edukacyjne; sukces edukacyjny; uczniowie